Peran Bagian Hukum Sekretariat Daerah Kabupaten Hulu Sungai Selatan Dalam Pembentukan Produk Hukum Daerah Yang Berkualitas - Zaki Yamani, Akhmad; Rafina; Yunita, Puteri (Zona Law And Public Administration Indonesia, 2024)
The aim of this study is to explain the function of the Legal Division of the Regional Secretariat of Hulu Sungai Selatan Regency in creating local legal products and to find things that support and hinder its implementation. This research used a qualitative and analytical approach. Observation, interview with the staff of law department and employees, and documentation surveys are the methods used to collect the data. The result of the research shows that the Legal Division plays an important role in arranging the draft regulation, legality check, collaboration with relevant agencies, law-building, and supervising the implementation of regional legal products. The competence and experience of the employee were the supportive factors found, while limited resources, ambiguity of authority, and differences in legal understanding between the parties involved were the impediments. This research is expected to provide both theoretical and practical benefits. Theoretically, this study adds insight into the role of the Legal Division in managing the regional governance. This research can help the local government, especially the Legal Division of the Regional Secretariat of Hulu Sungai Selatan Regency, improve the process of creating local legal products more efficiently and effectively. Therefore, this research helps to develop legal practices and policies at the regional level, improve the quality of regulation, and support for a better governance